Perspectief : de politieke doctrines in 1980 : een prognose - Lefèvre, Theo; Vranckx, Alfons; De Weerdt, Francis (Gent : Story-Scientia, 1968)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie